Legal Politics of Social Workers Law as an Advocacy Effort of Social Workers - Yasir, Al-; Haq, Muhammad Izzul; Ma’mun, Sukron; Prasetyo, Fitri Nur Aini (UIN Sunan Kalijaga Yogyakarta, 2023)
As the organizer of the realization of social welfare, the state has not been able to optimally overcome social changes, which have an impact on increasing the number and complexity of social welfare problems. With the arguments of humanity and the principle of mutual cooperation, some parties help the government, then are called social workers. To ensure their existence, social worker organizations in Indonesia initiated the formation of the Law on the Social Worker Profession. Law Number 14 of 2019 concerning Social Workers was formed. After the birth of this Law, some questions emerged whether the Law provided solutions to the problems faced by social workers in assisting social welfare, or with this Law, the state would be out of hand and emphasize the resolution of social problems to social workers. This study described the legal political conditions for forming this Law. This study answered the politics of the formation of Law Number 14 of 2019 and the challenges for Social Workers in Indonesia after the birth of the Law. Answering those problems, this study used—statute approach, historical approach, and conceptual approach, strengthened by some literature related to Law and social workers. Besides that, this study also used protection theory to assess the Law. This study also compared some regulations in some countries regarding social workers in some cases. In short, this study found that the strong historical background, the long existence of social workers in Indonesia, and the need for legal protection and certainty have become the reason for establishing Law No. 14, 2019. However, after the birth of the Law, challenges arose for social workers where their actualization was not easy and limited according to their profession and education. In addition, it is alleged that the Law could lead to malpractice because there are no sanctions. While in Australia, and USA, social worker laws give more space for social worker.